POTENTIAL ROLE OF OXIDATIVE STRESS AND ANTIOXIDANT DEFICIENCY IN PATHOGENESIS OF PSORIASIS - Dr.T.VIVIAN SAMUEL; Dr.KRISHNA MURARI (International Journal of Pharma and Bio Sciences, 2013)
Psoriasis is a common, chronic, inflammatory dermatological disorder with unknown aetiology.Alteration in concentrationof oxidants and antioxidants in serum lead to imbalance known as oxidative stress. This oxidative stress produces some biochemical and inflammatory changes in skin and is suggested as one of the etiopathological factor in development of psoriasis. The aim of our study was to evaluatethe levels of serum oxidants e.g. malondialdehyde and nitric oxide; and antioxidants e.g. superoxide dismutase and total antioxidant statusand correlation of these levels with severity of disease.In our research work we took 60 clinically diagnosed cases of psoriasis and 60 age and sex matched healthy controls.Our results showed increased concentration of oxidants: malondialdehyde, nitric oxide; and decreased concentration in antioxidants: superoxide dismutase,total antioxidant status in serum of psoriasis patients. Observations of our research work provide some evidence regarding the role of oxidative stress and antioxidant deficiency in pathogenesis of psoriasis.